Motion geometry - Abalos, Jose Alvares (University of the Philippines Diliman, 1972)
This paper introduced the basic motions involved in the study of geometry through transformation. Separate lessons and activities were developed to presnt these basic concepts to elementary school children and to inservice and preservice elementary school teachers.